1988
DOI: 10.1116/1.584071
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of poly(methylmethacrylate) by deep ultraviolet, x-ray, electron beam, and proton beam irradiations

Abstract: The chemical changes in poly(methylmethacrylate) (PMMA) caused by irradiation with deep ultraviolet (UV), x-ray, electron, and proton beams were studied by gel permeation chromatography, Fourier-transform infrared, and UV spectroscopy. The quantitative analysis of spectroscopic changes (Beer’s law) demonstrated a 1:1 correspondence between the disappearance of ester groups and the generation of double bonds in the polymer chain by all types of radiation. The ratio of main chain scission to changes in the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(83 citation statements)
references
References 0 publications
2
81
0
Order By: Relevance
“…5a, it is found that main-chain scission occurs from only 2.5% and 10% of the polymer radicals generated by benzoyl sidechain cleavage at 30°C and 130°C, respectively. The former value, 2.5%, is quite similar to the value of 2.6% observed with main-chain scission of PMMA after the ester side-chain removal (17). Compared with this, the ratio of 10% indicates much enhanced efficiency of main-chain scission at 130°C.…”
Section: -3supporting
confidence: 67%
See 1 more Smart Citation
“…5a, it is found that main-chain scission occurs from only 2.5% and 10% of the polymer radicals generated by benzoyl sidechain cleavage at 30°C and 130°C, respectively. The former value, 2.5%, is quite similar to the value of 2.6% observed with main-chain scission of PMMA after the ester side-chain removal (17). Compared with this, the ratio of 10% indicates much enhanced efficiency of main-chain scission at 130°C.…”
Section: -3supporting
confidence: 67%
“…Photosplitting of the ester side chains of PMMA generates polymer radicals, the structure of which is the same as those from PMMA-PIPK involving the benzoyl side-chain cleavage. PScission proceeds from only 2.6% of the polymer radicals and most of the radicals form C=C bonds in the main chain or the side chain (17) (Fig. 1, c (11 = 1) and d).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Although the picture is not entirely clear, there is a reasonable consensus as to the principal events that occur. 22 The initial absorption of radiation seems to lead to a scission (or chemical transformation) of the ester side chain of a monomer segment.…”
Section: Photochemistry Modelmentioning
confidence: 99%
“…Many fabrication methods of refractive micro-lens were reported (Ref [2][3][4][5][6][7][8][9][10][11][12][13], and most of which used photoresist reflow technique (Ref 2-7). Some micro-optical components were fabricated by molding (either hot embossing or injection molding) (Ref [14][15][16].…”
Section: Introductionmentioning
confidence: 99%